Clinical and magnetic resonance imaging study of extrapyramidal symptoms in multiple system atrophy. Issue 12 (December 1994) - Konagaya, M; Konagaya, Y; Iida, M
Abstract : Slit-hyperintensity in the outer margin of the putamen on T2 weighted MRI was found in 17 out of 28 patients with clinically diagnosed multiple system atrophy. Thirteen of these 17 patients showed extrapyramidal signs. Five patients had only unilateral slit-hyperintensity; four of them had contralateral rigidity; and one had bradykinesia. Despite mild rigidity, one case showed no slit-hyperintensity. One of the 14 cases with parkinsonism showed no hyperintensity, and four of the 14 cases without parkinsonism showed hyperintensity. On the other hand, slit-hyperintensity was not seen in any of 25 patients with clinically diagnosed Parkinson's disease. Putaminal slit-hyperintensity is a useful MRI feature in the differential diagnosis between Parkinson's disease and multiple system atrophy predominantly affecting the extrapyramidal system.